Computational analysis to investigate the anti-rheumatic potential of plant-based small molecule inhibitor targeting tumor necrosis factor α - Rehman, Sanaya; Bhatti, Attya; John, Peter (Frontiers in Pharmacology, 2023)
Objective: This study aimed to assess the anti-rheumatic potential of Dodonaea viscosa and to evaluate its bioactive small molecules for their beneficial effects in the management of rheumatoid arthritis. Methods:In vitro bioactivity assays were performed to assess the healing potential of D. viscosa and statistical analysis was performed by using the linear regression technique. In silico analysis was performed to identify the key inhibitors of the disease to target TNF-α. The plant extract was prepared using ethanol solvent via the Soxhlet method. Phytochemical and bioactivity testing was performed. Gas chromatography–mass spectrometry (GC-MS) analysis was conducted for bioactive plant compounds. Disease-specific target was shortlisted by HUB gene analysis. Molecular docking and molecular dynamic simulations were run for validation of the results. Results: Phytochemical studies verified the presence of phenols, flavonoids, steroids, sterols, saponins, coumarins, tannins, and terpenoids. The significant antioxidant potential of plant extract was evaluated by the DPPH and Ferric Reducing Antioxidant Power (FRAP) assays, while the anti-inflammatory potential was evaluated by the protein denaturation and Human Red Blood Cell (HRBC) membrane stabilization assays. In silico studies revealed that nine of the 480 compounds found in D. viscosa (ethanol extract) had drug-like properties. Tumor necrosis factor alpha (TNF-α) was selected as a key disease gene through HUB gene analysis. Results of molecular docking and MD simulation analysis demonstrated that 4-(1-hydroxy-3-oxo-1H-isoindol-2-yl) benzoic acid (PubChemID 18873897), had the best binding affinity with TNF-α amongst all nine compounds. Conclusion: 4-(1-hydroxy-3-oxo-1H-isoindol-2-yl) benzoic acid (PubChemID 18873897), have the potential to be a good small molecule inhibitor of TNF-α against rheumatoid arthritis.